Avaliação da alteração linear de fundições com liga de níquel-cromo, obtidas por meio de dois revestimentos fosfatados de diferentes composições - Goshi, Carlos Magno [UNESP] (2000)
This study evatuated the linear alteration of castings with NiCr alloy (Verabond II) obtained with two phosphate-bonded investments, one with granuled ceramic refractory load (Microfine 1700), which allows the introduction of the ring after setting directly in a pre-heated oven (750ºC); and another one, cristobalite-based (Bellavest-T) for conventional procedure. Forty wax patterns (Bredent life - color wachs, regular type II) were obtained through the direct molding of a stainless steel plate. Twenty wax patterns were invested in Microfine 1700 and twenty in Bellavest-T. A profile projector (0.001mm precision) measured the distance between 2 pre-established points in the matrix. The same distance was measured on the wax patterns and on the NiCr specimens produced, hereby obtaining the measure of the possible dimensional alterations of the materials. The results showed significance between the 2 investments (Bellavest-T, 5% and Microfine 1700, 1%) as compared to the matrix, through the Student's t test. The conclusions were: a) the two investments could not compensate the contraction of the alloy and wax in the casting process; b) the mean distance of the castings obtained with Microfine 1700, despite the fact of being smaller than the matrix and than the castings of Bellavest-T, showed more constant dimensions